(untitled) (Herald of Journalism, 2020)
The maximum success in modernization of the higher educational system in RK can be achieved in case all program directions of the Gov- ernment placed into educational policy take all the best possible from positive potential of the US higher educational system in main directions: qualitative selection of school-leavers, qualitative teaching staff, high level of organizing of teaching process, finance provision, development of the infrastructure of the university.